2014
DOI: 10.1186/2193-1801-3-693
|View full text |Cite
|
Sign up to set email alerts
|

Age and ultra-marathon performance - 50 to 1,000 km distances from 1969 – 2012

Abstract: We investigated age and performance in distance-limited ultra-marathons held from 50 km to 1,000 km. Age of peak running speed and running speed of the fastest competitors from 1969 to 2012 in 50 km, 100 km, 200 km and 1,000 km ultra-marathons were analyzed using analysis of variance and multi-level regression analyses. The ages of the ten fastest women ever were 40 ± 4 yrs (50 km), 34 ± 7 yrs (100 km), 42 ± 6 yrs (200 km), and 41 ± 5 yrs (1,000 km). The ages were significantly different between 100 km and 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…This seems to be a little bit low however when comparing with other concepts of distance and height the performance equivalent of 100 Meter ascents seems to be a little bit less than 1 km horizontal distance [30,31]. Analyses reveal that from the age of 35 a decrease in performance capacity results, which is in accordance with a number of other studies [2][3][4][5][6][7]32,33]. Trying to decipher reasons for the age associated decrease in endurance capacity besides the mentioned decrease in cardio-pulmonary system especially collagen tissue-ligaments and tendons-can be mentioned [34,35].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This seems to be a little bit low however when comparing with other concepts of distance and height the performance equivalent of 100 Meter ascents seems to be a little bit less than 1 km horizontal distance [30,31]. Analyses reveal that from the age of 35 a decrease in performance capacity results, which is in accordance with a number of other studies [2][3][4][5][6][7]32,33]. Trying to decipher reasons for the age associated decrease in endurance capacity besides the mentioned decrease in cardio-pulmonary system especially collagen tissue-ligaments and tendons-can be mentioned [34,35].…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, analyses reveal in Figure 7, that Napfmarathon with a regression weight of β=0.0369 is smaller than in city marathon with β=0.0487, in line with the before mentioned and implying, that the decrease in physical endurance performance in Napf marathon is smaller compared to city marathons. Besides other reasons the simple fact of the total larger amount of performance is probably one important reason [3,7,8,11,22]. The meter above sea level of the race (700 to 1400 Meter) respectively the effect of a smaller oxygen pressure doesn`t seem to be relevant while analyzing differences (e.g.…”
Section: Statistical Proceduresmentioning
confidence: 99%
“…The current age of elite marathoners is around 30 years for both males and females (Hunter et al, 2011), but the age of peak performance in endurance events generally increases as race distance increases (Knechtle et al, 2014; Romer et al, 2014). Interestingly, data from ultra-endurance events reported that the age of the elite athletes has increased over the past few decades as have their performances.…”
Section: Elite Ultra-endurance Athletes Get Oldermentioning
confidence: 99%
“…Although the age of peak marathon performance is at ~30-35 years (Hunter, Stevens, Magennis, Skelton, & Fauth, 2011;Lara, Salinero, & Del Coso, 2014), ultra-marathoners achieve their best performances at an older age, i.e. older than ~35 years (Cejka, Knechtle, Rüst, Rosemann, & Lepers, 2015;Romer et al, 2014;Rüst, Knechtle, Rosemann, & Lepers, 2013). Regarding the sex, the age of peak performance was older in women than men in marathon (Hunter, Stevens, Magennis, Skelton, & Fauth, 2011), whereas it was similar in women and men ultra-marathon runners competing in 100 km (Cejka, Knechtle, Rüst, Rosemann, & Lepers, 2015) and 100 miles races (Rüst, Knechtle, Rosemann, & Lepers, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Nevertheless, there are differences in the age of peak performance for ultra-marathons of different distances. Recent studies showed that the age of peak ultra-marathon performance increased with increasing race distance Romer, Rüst, Zingg, Rosemann, & Knechtle, 2014). Although the age of the best running performance in distancelimited ultra-marathon distances of 100 km (Cejka et al, 2015) and 100 miles (Rüst et al, 2013) is ~35 years, athletes competing in time-limited ultra-marathons such as 48 hours, 72 hours, 6 days and 10 days achieved their best performance at ~45-50 years ).…”
Section: Introductionmentioning
confidence: 99%